Al-Isytiqāq Bayna al-Qudamāʾ wa al-Muḥdathīn - Abdul Basith (Department of Arabic Teaching, Faculty Tarbiyah, Universitas Darussalam Gontor, 2015)
This article aims to examine the concept of derivation (ishtiqāq) from the perspectives of both classical and modern linguists. The topic occupies a central position in the study of the Arabic language because derivation is one of the distinctive characteristics that sets Arabic apart from many other languages of the world. Both classical and modern scholars classify derivation into several categories, all of which are based on its fundamental principle: deriving one word from another while preserving the root letters, the original lexical base, semantic relationship, and letter sequence, although certain changes may occur in one or more of these elements. Within these classifications, however, scholars differ regarding the original source of derivation. The primary debate concerns whether the verb or the verbal noun (maṣdar) constitutes the original form from which other words are derived. Among the classical grammarians, this disagreement is represented by the well-known positions of the Kufan and Basran schools. Modern linguists likewise hold differing views: some support one of these traditional positions, whereas others propose a new approach that departs from both by recognizing three original sources of derivation, a framework that has also influenced lexicographers in the compilation of Arabic dictionaries.